DAYA TOLAK REPELLENT BENTUK LOTION DENGAN EKSTRAK BUNGA KECOMBRANG (Nicolaia speciosa Horan) TERHADAP NYAMUK Aedes aegypti Linn - Layna Ratna Sari; Budiyono Budiyono; Retno Hestiningsih (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Dengue hemorrahagic fever is a public health problem that trasmitted by Aedes aegypti. The used of chemicals as mosquitos repellent may causing health problems. Natural repellent can be used, one of them is Kecombrang (Nicolaia speciosa Horan). Kecombrang containing alkaloid, flavanoid, saponin, and tanin compound which have repellency for mosquitoes.The purpose of this study was to determine the repellency lotion with extracts kecombrangagainst Ae. aegypti. This research is a quasi-experimental study with the approach of Post Test Only Control Group Design. The samples are 625 females ofAe aegypti. The analysis was usedKruskal-Wallis test. The results showed there were at least a statistically significant difference in the average of Ae aegypti mosquitoes that land on hands using lotions kecombrang with concentration 8%, 10%, 12%, 16%, and 20% with p = 0.001 (with a 95% confidence level and df = 4). Total Ae aegypti that landed in the hands fluctuated during the 6 hours of treatment. The largest repellency contained in concentration of lotion kecombrang 16% with an average protection66.8%. The development of plant-based insecticides should be developed as a safe repellent.